Updates in Breast Reconstruction Review from Evidence - Sisti, Andrea; Cuomo, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of manuscripts on breast reconstruction, the topic of a Special Issue of Medicina Journal. The book begins with a review of the literature on the most recent reconstructive strategies using biological dermal matrices and moves toward the management of pain and infections. Some aspects of regenerative surgery are also clarified and an analysis focuses on social disparities in access to breast reconstruction. The final part of this book is dedicated to nipple-areola reconstruction, the last surgical step of breast reconstruction.